Palladium‐Catalyzed Decarboxylative Cross‐Couplings of 1‐Boc‐3‐iodoazetidine: Regioselective Access to 2‐Alkynylazetidines, 3‐Alkynylazetidines and 3‐Vinylazetidines. Issue 12 (2nd May 2018) - Han, Shuaijun; Ren, Xiaoxiao; Wu, Qingsong; Liang, Apeng; Li, Jingya; Zou, Dapeng; Wu, Yangjie; Wu, Yusheng
Abstract: The first palladium‐catalyzed decarboxylative coupling reactions of alkynyl carboxylic acids or α, β‐unsaturated carboxylic acids with 1‐Boc‐3‐iodoazetidine were described. The strategy could efficiently mediate β‐hydride elimination/migratory insertion sequence and selectively form 2‐alkynylazetidines (10 examples) and 3‐alkynylazetidines (15 examples) with high regioselectivity. The protocol provides convienient access to a variety of useful 3‐vinylazetidines in moderate yields (42%–72%) with good stereoselectivity. Notable advantages of this method include easy operation, mild reaction conditions, and wide substrate scope. Abstract :